Protecting family members from the inside according to Quranic middle approach - Almansour, Naif Nasser (Journal of Islamic Sciences, 2023)
In Late times, groups of people appeared who distorted the meaning of the moderation of Islam and its applications on the ground. Indeed, there are groups of people who criticize commitment and integrity. Scholars regarding the protection of family members and their rights and duties, explaining the importance of reflecting on the Qur’an first, clarifying the meanings of moderation, mentioning the obstacles to education in the modern era, and mentioning the results of the research and the recommendations recommended by the researcher in this regard.